Avaliação da utilidade diagnóstica da procalcitonina e da proteína C reativa em pacientes críticos com síndrome respiratória aguda grave e suspeita de infecção pelo vírus influenza H1N1 2009 - Mariana Benevides Santos Paiva (2012)
During the 2009 influenza A H1N1 pandemic it became difficult to differentiate viral infection from other conditions in patients admitted to the Intensive Care Unit. We sought to evaluate the utility of circulating serum levels of procalcitonin and C-reactive protein to differentiate the 2009 influenza A H1N1 infection from other conditions in patients admitted to the intensive care unit with severe acute respiratory illness during the pandemic; and to investigate the behavior of circulating levels of four cytokines (tumor necrosis factor-, interferon-, interleukin-1 and interleukin-10) in those patients. To this, we performed prospective measurements of these molecules in 35 consecutive patients admitted to two University Hospitals intensive care units with suspected 2009 influenza A H1N1 pneumonia on admission and on days 3, 5 and 7. Three groups were constituted: (i) 12 (34.3%) patients with confirmed 2009 influenza A H1N1 infection; (ii) 6 (17.1%) patients with seasonal influenza infection; (iii) 17 (48.6%) patients with negative swabs for influenza virus. Circulating levels of PCT at inclusion and on day 3, and CRP on day 3, were significantly higher among subjects with confirmed 2009 influenza A H1N1 infection compared the other two groups of critically ill patients, p=0.005, p=0.015 and p=0.024, respectively. Regarding the tested cytokines, baseline levels of interleukin-1 were significantly higher among patients of 2009 influenza A H1N1 group compared to the other groups (p=0.014). CRP levels on day 3, 5 and 7 (p= 0.047, p=0.012 and p=0.008, respectively) and PCT levels on days 5 and 7 (p=0.019 and p=0.001, respectively), were significantly higher in non-surviving patients. In conclusion, we found higher levels of procalcitonin, C-reactive protein and interleukin-1 among critically ill patients with severe acute respiratory illness due to 2009 influenza A H1N1 compared to those cases related to seasonal influenza infection and non-influenza diagnoses. In the analysis including the 35 patients, procalcitonin on days 5 and on day 7, and C-reactive protein on days 3, day 5 and day 7 following admission were associated with all-cause hospital mortality.